Broad-spectrum Antibacterial Activity of Callistemon salignus Essential Oil against Foodborne, Waterborne, Environmental and Clinical Opportunistic Bacterial Pathogens - Omobolanle E. Oladapo; Mona M. E. Eleiwa; Sideeqot T. Abdullahi; Kehinde O. Amisu; Oladipupo A. Lawal; Emmanuel E. Aduak; Kanyinsola O. Akinkunmi; Victoria C. Dada; Olaide R. Tijani; Andy R. Opoku; Solayide A. Adesida (Advances in Research, 2026)
Aims: Microbial contamination of food and water constitutes a significant public-health risk worldwide, particularly because of the increasing prevalence of multidrug-resistant (MDR) opportunistic bacterial pathogens. The growing threat of antimicrobial resistance compromises the effectiveness of conventional antibiotics and highlights the need to explore alternative or complementary antimicrobial agents from natural sources, particularly medicinal plants and their derivatives. Therefore, this study aimed to comprehensively evaluate the antibacterial activity of Callistemon salignus (Sm.) Colvill ex Sweet (Myrtaceae) essential oil against a broad range of environmental, foodborne, waterborne, and opportunistic bacterial pathogens. Study Design: The study involved the extraction of essential oil from the leaves of C. salignus and the evaluation of its antibacterial activity against foodborne, waterborne, environmental, and opportunistic bacterial pathogens. Place and Duration of Study: Fresh, healthy leaves of C. salignus were collected during the flowering season from mature plants growing on the KwaDlangezwa campus of the University of Zululand, KwaZulu-Natal Province, South Africa. Methodology: Twenty (20) Gram-positive and Gram-negative bacterial isolates obtained from foodborne, waterborne, environmental, and clinical sources were tested for susceptibility to C. salignus essential oil using the agar disc diffusion assay. Minimum inhibitory concentrations (MICs) were established by broth microdilution, while minimum bactericidal concentrations (MBCs) were determined by subculturing aliquots from wells showing no visible bacterial growth onto Mueller–Hinton agar. MBC/MIC ratios were calculated to assess bactericidal and bacteriostatic activity. Ciprofloxacin was used as the reference antibiotic. Comparative antibacterial activity was visualised using a Cleveland dot plot, while integrated heatmap analysis and hierarchical cluster analysis were used to evaluate similarities in bacterial susceptibility profiles. All experiments were performed in triplicate, and data were expressed as mean ± standard deviation. Statistical significance was assessed using one-way analysis of variance (ANOVA) followed by Tukey's multiple comparison test, with statistical significance set at P ≤ 0.05. Results: Callistemon salignus essential oil inhibited 18 of the 20 (90%) bacterial isolates tested, producing inhibition zones ranging from 9.0 ± 0.0 to 12.0 ± 0.0 mm. MIC values ranged from 2.5 to >5.0 mg/mL, while MBC values ranged from 2.5 to >5.0 mg/mL. Most reported susceptible isolates exhibited MBC/MIC ratios within the bactericidal threshold (≤4). Ciprofloxacin demonstrated significantly greater antibacterial activity (P < 0.05) than the essential oil, although C. salignus exhibited inhibitory and bactericidal activity against both Gram-positive and Gram-negative bacteria. Integrated heatmap analysis revealed differences in susceptibility across the bacterial panel, while hierarchical cluster analysis grouped isolates according to their overall antibacterial response. Conclusion: Callistemon salignus essential oil exhibited broad-spectrum antibacterial and predominantly bactericidal activity against a diverse collection of foodborne, waterborne, environmental and clinical opportunistic bacterial pathogens. Integration of conventional antibacterial assays with multivariate analytical approaches provided a broader assessment of bacterial susceptibility and supported further investigation of the essential oil as a potential plant-derived antimicrobial agent. Further studies are recommended to identify the active constituents, elucidate their mechanisms of action, evaluate antibiofilm activity, assess toxicity, and investigate synergistic interactions with conventional antibiotics.